Increased Neutralizing Antibody Production and Interferon-γ Secretion in Response to Porcine Reproductive and Respiratory Syndrome Virus Immunization in Genetically Modified Pigs - Huang, Guangping; Liu, Xianyong; Tang, Xiaoli; Du, Li; Feng, Wenhai; Hu, Xiaoxiang; Zhu, Liangquan; Li, Qiuyan; Suo, Xun (Frontiers in Immunology, 2017)
T cell-mediated immunity plays a prominent role in combating pathogens infection. Both the engagement of the T cell receptor with the peptide-bound major histocompatibility complex and a co-stimulatory signal are needed for the complete activation of the T cell. To determine whether host immune responses to vaccination could be improved by enhancing CD28-mediated co-stimulation, and verify whether the boosted immune responses could protect the host against viral challenge, we produced a transgenic pig line expressing an extra copy of the CD28 gene controlled by its own promoter at the Rosa26 locus. As expected, in response to porcine reproductive and respiratory syndrome virus strain (PRRSV) vaccination, CD4+ T cells was remarkably increased in CD28 transgenic pigs and a similar response in CD8+ T cells was elicited after challenge. Importantly, because of increased T cell frequencies, the virus-neutralizing antibody against JXA-1 (a highly pathogenic Chinese PRRSV strain), as well as IFN-γ secretion, were enhanced in transgenic pigs. These findings in our translational study provide a novel concept for farm animal breeding in disease resistance, in which we may use the transgenic technology to force over-expression of confirmed immunity-promoting molecules like CD28 and produce an animal with enhanced immune responses to vaccination and broad-spectrum resistance to infectious diseases.